2022
DOI: 10.3390/ijns8010012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the GSP Creatine Kinase-MM Assay and Assessment of CK-MM Stability in Newborn, Patient, and Contrived Dried Blood Spots for Newborn Screening for Duchenne Muscular Dystrophy

Abstract: Duchenne Muscular Dystrophy (DMD) is a fatal X-linked disorder with a birth prevalence of 19.8:100,000 males worldwide. Elevated concentration of the muscle enzyme creatine kinase-MM (CK-MM) allows for presymptomatic screening of newborns using Dried Blood Spots (DBS). We evaluated imprecision and carryover of the FDA-approved PerkinElmer GSP Neonatal CK-MM kit over multiple runs, days, and operators, followed by quantification of CK-MM loss in stored newborn, contrived, and non-newborn patient DBS resulting f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…For NBS programs to establish and sustain DMD screening, laboratories will need reliable access to external QC materials to validate assays, conduct stability studies [ 20 ], ensure the consistency of test results, and meet regulatory requirements [ 15 ]. QC over a wide range is important, since CK-MM levels are variably elevated by birth trauma and then decline in the early post-natal period [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For NBS programs to establish and sustain DMD screening, laboratories will need reliable access to external QC materials to validate assays, conduct stability studies [ 20 ], ensure the consistency of test results, and meet regulatory requirements [ 15 ]. QC over a wide range is important, since CK-MM levels are variably elevated by birth trauma and then decline in the early post-natal period [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have piloted screening with quantitative detection of the CK-MM isoform as a specific biomarker of muscle damage using the FDAapproved GSP neonatal CK-MM kit (#3311-001U, PerkinElmer) [25,26].…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…In December 2019, the FDA approved the first-tier screen kit for DMD, which measures the level of creatine kinase-MM in dried blood spots. The test kit is high throughput and provides a method for universal screening of DMD in newborns (Chien et al, 2022;Ke et al, 2017;Migliore et al, 2022;Moat et al, 2017;Parad, Sheldon, & Bhattacharjee, 2021;Timonen et al, 2019). Data from pilot studies indicate that the assay can also detect other muscular dystrophies (Ke et al, 2017;Timonen et al, 2019) However, the mother, who later identified herself as a carrier, declined to submit another specimen for testing or follow-up.…”
Section: Mechanism Of Severe Disease In Femalesmentioning
confidence: 99%
“…Currently in the United States, DMD is not included as a condition on the Recommended Uniform Screening Panel (RUSP), and no states are routinely screening for DMD. However, pilots are underway or recently completed in three states (Hartnett et al, 2022 ; Migliore et al, 2022 ; Parad, Sheldon, & Bhattacharjee, 2021 ), a RUSP nomination package has been submitted, and at least one state is considering adding DMD to their panel. This increase in support for DMD NBS is consistent with an overall movement to more broadly consider this disorder for NBS, recognizing benefits beyond medical treatment, which often includes avoiding a diagnostic odyssey, family planning, and enrollment in early childhood intervention services, as discussed by Chung et al ( 2022 ).…”
Section: Introductionmentioning
confidence: 99%